Afghanistan: Challenges and Attitudes - Hayward, Fred; Amiryar, Sara (International Higher Education, 2004)
In an effort to obtain a sense of public perceptions and attitudes about higher education in Afghanistan after 25 years of war, we conducted 14 focus groups in Herat, Kabul, Kapesa, and Kundoz provinces during June and July 2003, as part of a project conducted for the Ministry of Higher Education by the Academy for Educational Development funded by the International Development Agency. The focus groups included high school and college students, parents, college and university instructors, school teachers, business people, and women professionals.